Toxinological profile and histopathological alterations induced by Bothrocophias campbelli venom from Colombia - Sevilla Sánchez, María José (2024)
Snakebite envenomings most frequently reported in Colombia are caused by snakes of the genera Bothrops, Bothriechis, Bothrocophias, and Porthidium. Their venoms induce local and systemic pathophysiological effects, sometimes leading to permanent sequelae such as reduced mobility of the limbs, amputations, besides the risk of death. The genus Bothrocophias includes nine species, among which B. campbelli has a distribution restricted to the department of Nariño in Colombia. In this work we determined the toxinological profile its venom, by performing assays for the lethal, hemorrhagic, edematogenic, and myotoxic activities in mouse models, as well as for in vitro coagulant activity on human plasma. The lethal toxicity of the venom was 142.7 µg venom/mouse (111.4–179.8 µg/mouse; 6.6–10.6 µg/g body weight) by intraperitoneal route. Its hemorrhagic activity (minimum hemorrhagic dose: 12.7 ± 2.3 µg) is generally weaker compared to other South American vipers, but edematogenic (minimum edematogenic dose 1.0 ± 0.3 µg), and myotoxic (minimum myotoxic dose 3.9 ± 2.5 µg) activities are very potent. Histopathological examination of the injected mouse gastrocnemius muscle showed prominent disorganization of the myofibrils, myonecrosis, and an intense inflammatory leukocyte infiltrate. In vitro, the minimal coagulant dose was 12.3 ± 0.5 µg. Overall, this toxinological profile would predict that the clinical picture of envenomings by B. campbelli might be characterized by moderate disturbances in the coagulation cascade, mild local hemorrhage, and, conversely, severe myonecrosis and edema, which could potentially lead to compartment syndrome and gangrene.